Offsetting behavior in reducing high cholesterol: Substitution of medication for diet and lifestyle changes - Lisa Mancino; Fred Kuchler (Journal of Choice Modelling, 2009)
Being diagnosed with a diet-related health condition like high blood cholesterol might compel an individual to choose a healthier diet, thereby reducing disease risks. Adding the option of medication, like statins, makes the direction of diet-quality choices theoretically ambiguous. This study estimates how dietary quality correlates with high cholesterol diagnoses and medicine use. Results indicate that individuals diagnosed with high cholesterol consume less cholesterol, fat, and saturated fat, and smoke less. However, using cholesterol-lowering drugs is correlated with increased fat and saturated fat intake, and larger waist size, after accounting for the endogeneity of choosing to use medicine. Findings highlight the inelasticity of diet choices.
Keywords: 330; offsetting behaviour; cholesterol; diet; medication